Rubber composition for inner liner of pneumatic vehicle tire

By using hydrothermal treatment modified Linsu as filler, combined with neoprene or bromine rubber, the surface characteristics and particle size distribution of the filler are optimized, and the existing inner tube rubber composite materials are solved, and the problems of high fuel consumption, large carbon emissions and filler environment are achieved, and a high-performance and low-carbon inner tube rubber composite materials are realized.

JP2025510045APending Publication Date: 2025-04-14SUNCOAL INDS GMBH

Patent Information

Application Number
JP2024556268
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-03-22
Filing Date
2023-03-22
Publication Date
2025-04-14

AI Technical Summary

Technical Problem

While existing inner tube rubber composites meet air sealing and crack resistance, it is difficult to effectively reduce fuel consumption and carbon emissions. At the same time, the use of oil-derived carbon black fillers has environmental problems.

Method used

Biomass-based fillers made of recycled raw materials, especially HTT lignon (HTT lignon) modified by hydrothermal treatment, are used as the main fillers, combined with neoprene or bromobutyl rubber, and by optimizing the surface characteristics and particle size distribution of the fillers, a high-performance inner tube rubber composite material is formed.

Benefits of technology

The low fuel consumption, low carbon emissions and high air sealing of inner tube rubber composite materials have been achieved, reducing the dependence on petroleum carbon black fillers, and the efficiency and environmental protection of the fillers have been significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025510045000001
    Figure 2025510045000001
  • Figure 2025510045000002
    Figure 2025510045000002
  • Figure 2025510045000003
    Figure 2025510045000003
Patent Text Reader

Abstract

The present invention relates to a rubber composition comprising a rubber component having at least one halobutyl rubber in an amount of 60 to 100 phr and a carbon content in the range of 0.20 to 0.45 Bq / g. 14 C content; carbon content in the range of 60% by mass to 85% by mass; and a filler component including a filler F1 having an acidic hydroxyl group on a surface thereof, wherein the weighted arithmetic mean of the STSA surface area of ​​the filler F1 is 40 m 2 / g~80m 2 / g; the filler F1 has a volumetric median particle size distribution Dv(50) in the range of 0.5 μm to 5 μm, and a volumetric Dv(97) value in the range of 3 μm to 23 μm; (i) the filler component contains more than 45 phr of filler F1; or (ii) the filler component contains more than 25 phr of filler F1 and further one or more carbon blacks F2, the weighted arithmetic mean STSA surface area of ​​the carbon blacks F2 being greater than 55 m 2 / g~95m 2 The present invention also relates to a vulcanizable rubber composition and a vulcanized rubber composition based on the aforementioned rubber composition, a kit of parts for producing the vulcanizable rubber composition, and a method for producing the rubber composition and the vulcanizable rubber composition. The present invention further relates to a method for further processing the vulcanizable rubber composition. The present invention further relates to the use of the aforementioned hydrothermally treated lignin for producing a rubber composition for an inner liner.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a rubber composition, more particularly to a vulcanizable rubber composition and a vulcanized rubber composition for an innerliner of a pneumatic vehicle tire.The present invention further relates to a kit of parts for producing the composition, a method for producing and further processing the composition, and a method for producing a pneumatic tire.The present invention further relates to the use of specialty fillers made from recycled raw materials for producing a rubber composition, in particular a rubber composition for an innerliner. [Background technology]

[0002] Pneumatic vehicle tires have a complex structure. The requirements made on them are correspondingly diverse: on the one hand, they must ensure short braking distances on dry and wet roads, on the other hand, they must have good wear properties and low rolling resistance. In addition, vehicle tires must meet the requirements of the legislature.

[0003] To ensure these diverse performance profiles, the individual tire components are specialized and made from a number of different materials, including metals, polymeric fiber materials, and various rubber-based components.

[0004] Depending on the design of the pneumatic tire, a distinction is made between radial, cross-ply, bias-ply or bias-belted tires. A typical pneumatic tire, for example a radial-ply belted tire, comprises at least a belt, a belt cover, a tread, a reinforcing strip, sidewalls, a bead filler, a bead wire, an inner liner and a carcass.

[0005] The belt usually consists of layers of rubber-coated, angled steel strands. The main purpose of the belt is to give the tire structural strength when inflated. The belt also gives the tire running stability during acceleration, braking and cornering. The belt influences the rolling resistance, which is a major contributor to the tire's fuel economy.

[0006] A belt overlay, located between the tread and the upper belt, improves high speed performance and serves to limit the tire diameter as speed increases.

[0007] The tread is essentially responsible for the driving properties. The rubber compound of the tread determines the wear and dynamic driving properties in different weather conditions (wet and dry roads, cold and warm weather, on ice and snow). The design of the tread pattern greatly influences the tire's behavior in aquaplaning, in wet conditions and on snow and also determines its noise behavior.

[0008] To further improve the strength and running characteristics of the tire, reinforcing strips are optionally used in some cases in the bead filler area.

[0009] The sidewalls protect the carcass from lateral damage and atmospheric influences. The rubber compound of the sidewalls is flexible, abrasion resistant, and contains a relatively high amount of aggregates for protection against degradation and ozone.

[0010] The bead filler sits on top of the bead wire / bead core. The shape and configuration of the bead filler provide driving stability and influence steering precision and suspension comfort. Rubber compounds for bead fillers are typically very strong and relatively hard. This property is ensured, among other things, by a high degree of cross-linking using a high-additive vulcanization system and the choice of filler.

[0011] The bead wire is the inner part of the tire bead, consisting of a rubber-coated steel strand wound into a ring, which holds the tire stably on the rim. In a typical tubeless construction, the tire bead (also called the tire base or foot) is pressed against the flange of the rim, sealing the tire. The steel cords and wires in the bead core, tread, or carcass of a full steel tire must have a firm connection with the surrounding rubber compound to function as a composite. For this reason, the steel wires are often coated with brass or bronze. They are then formed into tire components using a wire bonding compound, and the components are assembled to form the tire blank. Wire bonding compounds have a relatively high strength and crack resistance due to their high percentage of natural rubber, and provide a strong connection with the brass or bronze coating, for example, through special resin additives and high sulfur content. A permanent connection is formed during vulcanization.

[0012] The carcass forms the basic structure of the tire and consists of one or more layers of fabric (rayon, nylon, polyester, aramid) or steel cords (for trucks) embedded in rubber. The carcass is tensioned by the air pressure in the tire and is therefore essentially responsible for the force transmission between the rim and the tread / road. It is connected to the tire beads of the tire base and holds the tire together. It acts as a composite between the cord layers, which ensure strength and force transmission, and the rubber compound that encases the parallel cords. Since the tire is constantly deforming, the cord compound must be fatigue resistant. This is most often achieved by a blend of natural and synthetic rubber, but the cord compound must also form a stable connection with the cords. For this purpose, the cords are coated with a rubber compound after laying / twisting. The cords with their finish are then coated with an unvulcanized rubber compound. The resin system in the special compound then reacts with the cord finish during vulcanization to form a durable composite.

[0013] Modern tires are usually tubeless as mentioned above. The so-called inner liner is a layer of rubber compound arranged radially inside and is as airtight as possible. The inner liner, also called inner core or inner plate, is used to ensure that the air pumped into the tire does not escape for a long time, since the air pressure significantly affects the running characteristics and durability of the tire. In addition, the internal pressure also affects the rolling resistance of the tire. A decrease in air pressure leads to greater dynamic deformations of the tire, which causes an undesirable conversion of part of the kinetic energy into thermal energy. This has a negative effect on the vehicle's fuel consumption and the associated carbon dioxide emissions.

[0014] In addition, the innerliner protects the carcass from the diffusion of air and moisture into the carcass and prevents damage to the strength elements of the carcass and / or belt. In order for the innerliner to maintain maximum airtightness, it should also have good crack and fatigue resistance to prevent cracks from developing during driving that could affect the airtightness.

[0015] Due to these special required properties, the rubber compound for the innerliner has a completely different composition from the rubber compounds for other tire components in terms of the rubbers and fillers used and the relative mass ratios of the components, but it must be compatible with the adjacent tire components, and in particular, must have good adhesion to those components. In addition to the type of rubber, the minimum amount of different rubbers in the rubber compound also plays a role, as well as various specific parameters and properties of the fillers that can be used.

[0016] In particular, halobutyl rubbers such as chlorobutyl rubber and bromobutyl rubber are sometimes blended with other rubbers and used as rubbers for inner liners. Butyl rubber and halobutyl rubber have low gas permeability. Blending of halobutyl rubber with other rubbers, such as natural rubber, is carried out for reasons such as increasing tack during assembly, reducing costs, and adjusting mechanical properties.

[0017] The gas tightness can be further improved by adding large amounts of additional low or no activity fillers to the rubber compound of the innerliner. Fillers that have been used so far include furnace carbon black, among others.

[0018] In order to prevent crack formation under dynamic load, the innerliner must have a balanced modulus and suitable hardness, which is usually in conflict with a high proportion of inactive fillers. Therefore, mineral oil-based softeners are often added to rubber compositions. The softeners reduce the modulus and hardness of the composition, but at the same time increase gas permeability again, so the optimal range of the mineral oil-based softener and filler usage is relatively narrow.

[0019] In addition, many fillers, such as type N660 carbon black, have a viscosity of about 1.8 g / cm 3 The filler has a relatively high density of 10 ...

[0020] Industrial carbon black is usually produced petrochemically by incomplete combustion or pyrolysis of hydrocarbons. However, the use of fossil energy sources for the production of fillers must be avoided or minimized from an environmental perspective. Instead, the aim should be to provide a biomass-based compounding filler that meets the diverse requirements of innerliners.

[0021] In the field of preparing rubber compositions for use in tires in general, WO 2017 / 085278 A1, inter alia, discloses the use of lignin converted by hydrothermal treatment, so-called HTT lignin, as a filler replacing technical carbon black.

[0022] Lignin is a solid biopolymer that is incorporated into plant cell walls, resulting in the lignification of the plant cells, and therefore, when contained in biologically regenerated feedstocks, especially in hydrothermally treated form, has the potential to be an environmentally friendly alternative to industrial carbon black in rubber compositions.

[0023] WO 2017 / 194346 A1 describes the use of HTT lignin in rubber compounds of pneumatic tire components, in particular in combination with methylene donor compounds, such as hexa(methoxymethyl)melamine, and / or in combination with silane coupling agents, to increase the stiffness of the cured rubber components of pneumatic tires, in particular to replace phenolic resins. One of the objectives set out in WO 2017 / 194346 is to decrease the rolling resistance of tires. Suitable rubber materials include natural rubber, polybutadiene rubber, styrene butadiene rubber and polyisoprene rubber. WO 2017 / 194346 A1 discloses the suitability of the rubber compounds described therein for the tread, sidewall and tire beads of pneumatic tires. No rubber compounds are described therein that meet the requirements of innerliners.

[0024] EP 3470457 A1 also discloses a vulcanizable sulfur-containing rubber compound for vehicle tires. The fillers used in the tested solvent-polymerized styrene butadiene rubbers (SSBR) were obtained from various feedstocks and produced with the addition of metal halides, with a maximum content of 180 m. 2 The HTT coals showed a BET surface area of ​​more than 90 to 140 m / g. 2 / g HTT coal was found to be particularly preferred as it is said to improve surface roughness and optimize surface functionality.

[0025] WO 2020 / 202125 A1 is the first to teach the use of halobutyl rubber in combination with up to 45 phr (parts by weight per 100 parts by weight of rubber) of HTT lignin in the field of innerliner manufacture, but in the examples of WO 2020 / 202125 A1 HTT lignin is not used as the sole filler, but exclusively in combination with carbon black of type N660. In particular, the aforementioned document shows that the added carbon black is 30-50 m 2 / g, which is 35 m 2 / g BET surface area (ASTM D 6556) and 34 m 2 / g STSA surface area (ASTM D 6556). However, the HTT lignin content is limited to a maximum of 45 phr and the incorporation of carbon black is limited to a maximum specific surface area of ​​50 m 2 It has been found that limiting the amount of carbon black to 1000 ppm / g is unexpectedly detrimental in terms of both reducing gas permeability and suppressing crack growth, even though the latter carbon black is typically used in innerliners.

[0026] Therefore, taking a comprehensive look at the state of the art, there is a particular need for a rubber composition or rubber compound suitable for pneumatic tire innerliners, containing an environmentally friendly material based on recycled raw materials as a filler as an alternative to carbon black, which meets the requirements of pneumatic tire innerliners, especially airtightness and crack resistance, and results in a vulcanized rubber composition with improved tear propagation resistance. [Prior art documents] [Patent documents]

[0027] [Patent Document 1] International Publication No. 2017 / 085278A1 [Patent Document 2] International Publication No. 2017 / 194346A1 [Patent Document 3] European Patent No. 3470457A1 [Patent Document 4] International Publication No. 2020 / 202125A1 [Non-patent literature]

[0028] [Non-Patent Document 1] "Determination of surface-accessible acidic hydroxyls and surface area of ​​lignin by cation dye adsorption" (Bioresource Technology 169 (2014) 80-87) [Non-Patent Document 2] "Kautschuk Technologie - Werkstoffe Verarbeitung Produkte" (3rd revised and expanded edition, 2013, pages 1196-1197) Summary of the Invention [Means for solving the problem]

[0029] The problem underlying the present invention is a rubber composition comprising: A rubber component including at least one halobutyl rubber selected from the group consisting of bromobutyl rubber and chlorobutyl rubber; In the range of 0.20 to 0.45 Bq / g carbon 14 C content; The carbon content is in the range of 60% by mass to 85% by mass of the filler, excluding ash and moisture, Has acidic hydroxy groups on the surface A filler component comprising one or more fillers F1; Including, The weighted arithmetic mean of the STSA surface area of ​​filler F1 is 40m 2 / g~80m 2 in the range / g; Filler F1 has a volume-based median particle size distribution Dv(50) in the range of 0.5 μm to 5 μm, and a volume-based Dv(97) value in the range of 3 μm to 23 μm; i. the filler component contains more than 45 phr of filler F1; or ii. The filler component comprises more than 25 phr of a filler F1 and further comprises one or more technical carbon blacks F2, the weighted arithmetic mean STSA surface area of ​​the technical carbon blacks F2 being greater than or equal to 55 m 2 / g~95m 2 in the range / g; The problem can be solved by providing a rubber composition, in which the amount of halobutyl rubber in the rubber composition is 60 to 100 phr.

[0030] The phr (parts per hundred parts rubber) designation used herein is a quantity designation commonly used in the rubber industry in compounding. The parts by weight addition of individual components is always based on 100 parts by weight of the total weight of all rubbers present in the compound.

[0031] This rubber composition is hereinafter also referred to as the rubber composition according to the present invention or the rubber composition of the present invention.

[0032] The present invention further relates to a vulcanizable rubber composition comprising or consisting of a rubber composition according to the invention and a vulcanization system containing zinc oxide and / or sulfur.

[0033] This vulcanizable rubber composition is hereinafter also referred to as the vulcanizable rubber composition according to the present invention or the vulcanizable rubber composition of the present invention.

[0034] A further object of the invention is a kit-of-parts comprising, in spatially separated form, a rubber composition according to the invention and a vulcanization system containing zinc oxide and / or sulfur.

[0035] This kit of parts is also referred to below as a kit of parts according to the invention (kit of parts) or as a kit of parts according to the invention.

[0036] Another object of the invention is a process for preparing the rubber composition according to the invention and the vulcanizable rubber composition according to the invention, the latter being obtained in a first stage by preparing the rubber composition according to the invention as a base compound (masterbatch) by compounding the constituents of the rubber composition and in a second stage by admixing the constituents of the vulcanization system.

[0037] These processes are also referred to as processes according to the invention for preparing the rubber composition according to the invention or the vulcanizable rubber composition according to the invention.

[0038] Another object of the invention is a method for further processing the vulcanizable rubber composition according to the invention, in which said composition is shaped into a web by calendering, extrusion or the so-called roller head process.

[0039] The method is also referred to as the method for further processing according to the invention or as the method for further processing according to the invention.

[0040] Another object of the invention is a method for manufacturing a pneumatic tire, comprising the further processing method according to the invention, followed by a step of cutting the web obtained to the size of the innerliner of a pneumatic tire, and then a step of vulcanizing the innerliner thus obtained, preferably together with the carcass of the pneumatic tire.

[0041] This method is also called the method according to the invention for manufacturing a pneumatic tire or the method according to the invention for manufacturing a pneumatic tire.

[0042] Another object of the present invention is the use of the fillers F1 and filler mixtures comprising F1 and F2 as characterized above, which are suitable in the context of the present invention, in rubber compositions for innerliners, where the fillers F1 and F2 are used in a total amount of at least 46 phr.

[0043] This use is also referred to as the use according to the invention or the use of the invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0044] In the following, the rubber composition components respectively used in the rubber composition, the above mentioned methods and uses, as well as particularly preferred process sequences are explained in detail.

[0045] <Rubber composition> Rubber In the context of the present invention, one or more halobutyl rubbers are used, selected from the group consisting of chlorobutyl rubber (CIIR; chloroisobutene isoprene rubber) and bromobutyl rubber (BIIR; bromoisobutene isoprene rubber).

[0046] Halobutyl rubber is a halogenated isobutene isoprene rubber. It can be obtained by halogenation, in particular bromination and / or chlorination, of butyl rubber.

[0047] Butyl rubber is mainly composed of isobutene units, and the remaining portion is isoprene units. Particularly preferably, the ratio of isobutene units is 95-99.5 mol%, the ratio of isoprene units is 0.5-5 mol%, more preferably, the ratio of isobutene units is 97-99.2 mol%, the ratio of isoprene units is 0.8-3 mol%, and the ratio of isobutene units and isoprene units is preferably 100 mol% in total of the monomers contained in the polymer and polymerized. Butyl rubber generally has low gas permeability and moisture permeability.

[0048] Because the isoprene units are polymerized, butyl rubber has carbon-carbon double bonds that lend themselves to both vulcanization and modification, especially with halogens such as chlorine and bromine.

[0049] Halobutyl rubber, which can be obtained by modification with halogens (halogenation), is more reactive than butyl rubber and therefore offers greater possibilities for vulcanization, for example co-vulcanization with other rubbers, such as natural rubber (NR), butyl rubber (IIR; isobutene-isoprene rubber) and styrene-butadiene rubber (SBR), among others.

[0050] Among halobutyl rubbers, bromobutyl rubber has a weak carbon-bromide bond, which makes it more reactive than chlorobutyl rubber, which has a carbon-chlorine bond, and this allows for a wider range of vulcanization systems for bromobutyl rubber. Bromobutyl rubber has a faster vulcanization rate and usually has good adhesion to diene rubbers.

[0051] Among the halobutyl rubbers, bromobutyl rubber is particularly preferred in the context of the present invention.

[0052] However, it is also possible to use, as the halobutyl rubber component, a compound of one or more bromobutyl rubbers with one or more chlorobutyl rubbers, where the bromobutyl rubber increases the vulcanization rate.

[0053] The chlorobutyl rubbers (CIIR) suitable in the context of the present invention preferably contain 1.1 to 1.3% by weight of chlorine, and the bromobutyl rubbers (BIIR) preferably contain 1.9 to 2.1% by weight of bromine, which corresponds to a proportion of reactive sites of about 2 mol %.

[0054] The viscosity of the halobutyl rubber is preferably comprised between 35 and 55 Mooney units (ML(1+8) at 125°C). Like butyl rubber, the product contains few secondary components (rubber ratio >98.5). The halobutyl rubber preferably contains stabilizers, in particular sterically hindered phenols, as stabilizers.

[0055] The rubber composition according to the invention may contain, in addition to the halobutyl rubber, one or more further rubbers different from the halobutyl rubber.

[0056] Particularly preferred as further rubbers different from halobutyl rubber, if present, are natural rubber, butyl rubber and styrene butadiene rubber.

[0057] For example, the incorporation of natural rubber into halobutyl rubber can improve adhesion to other rubber-based tire components, especially compared to general-purpose rubbers. Crosslinking different rubbers can create synergistic effects in terms of tensile strength that can exceed that of the individual rubbers. This is especially true when using vulcanization systems that include zinc oxide, sulfur, and thiazoles, such as mercaptobenzothiazole disulfide (MBTS). Meanwhile, the gas and moisture permeability of the vulcanized end product is typically increased by the incorporation of natural rubber.

[0058] Styrene-butadiene rubber can be incorporated into halobutyl rubber in a similar manner to the incorporation of natural rubber, but the use of natural rubber is usually preferred over the use of styrene-butadiene rubber, as it typically offers no particular advantages over the latter, and also in terms of the use of renewable resources. For example, typical natural rubber is sold under the names SMR ("Standard Malaysian Rubber"), TSR ("Technically Specified Rubber"), and RSS ("Ribbed Smoked Sheets").

[0059] Incorporation of butyl rubber into the halobutyl rubber at up to 30 phr, preferably up to 20 phr, typically has little or no effect on the gas and moisture permeability of the final vulcanized product, but can slow the vulcanization rate and increase heat resistance, if desired.

[0060] The total amount of halobutyl rubber is 60 to 100 phr, preferably 65 to 100 phr, particularly preferably 70 to 100 phr, further preferably 75 or 80 to 100 phr, more preferably 85 or 90 to 100 phr, for example 95 to 100 phr, and most preferably 100 phr.

[0061] If the rubber compound contains less than 100 phr of halobutyl rubber, the rubber composition contains at least one other rubber, preferably one of the rubbers listed above, more preferably natural rubber, to bring the total amount of rubber contained therein to 100 phr.

[0062] This means that the amount of rubber other than the halobutyl rubber is 0 to 40 phr, preferably 0 to 35 phr, particularly preferably 0 to 30 phr, further preferably 0 to 20 or 25 phr, more preferably 0 to 10 or 15 phr, for example 0 to 5 phr or 0 phr.

[0063] Filler F1 The filler components always used are: 0.20-0.45Bq / g carbon, preferably 0.23-0.42Bq / g carbon 14 C content; one or more fillers F1 having a carbon content in the range of 60% to 85% by weight, preferably 63% to 80% by weight, particularly preferably 65% ​​to 75% by weight, more preferably 68% to 73% by weight, based on the ash- and moisture-free filler; The weighted arithmetic mean of the STSA surface area of ​​filler F1 is 40m 2 / g~80m 2 / g, preferably 42m 2 / g~75m 2 / g, more preferably 44m 2 / g~70m 2 in the range / g; the one or more fillers F1 have a volume-based median particle size distribution Dv(50) in the range of 0.5 μm to 5 μm, particularly preferably 1 μm to 4 μm, more preferably 1 μm to 3 μm, and a volume-based Dv(97) value in the range of 3 μm to 23 μm, preferably at most 18 μm, particularly preferably at most 15 μm, more preferably at most 12 μm, even more preferably at most 10 μm, even more preferably at most 9 μm, even more preferably at most 8 μm, most preferably at most 7 μm, more preferably at most 6 μm; The filler or fillers F1 have acidic hydroxy groups on the surface.

[0064] The necessary 14 The C content is realized by the filler F1 obtained from biomass by further processing or reaction, preferably decomposition, which can be carried out thermally, chemically and / or biologically, preferably thermally and chemically. Thus, in particular fillers obtained from fossil materials such as fossil fuels can be treated with the corresponding 14 Since it does not have a C content, it does not fall within the inventive definition of the fillers used according to the invention.

[0065] Biomass is defined herein as, in principle, any biomass, including so-called phytomass, i.e. biomass derived from plants, zoomass, i.e. biomass derived from animals, and microbial biomass, i.e. biomass derived from microorganisms, including fungi, which may be dry or fresh biomass and derived from dead or living organisms.

[0066] Herein, a particularly preferred biomass for the preparation of the filler F1 is phytomass, preferably dead phytomass. Dead phytomass includes, inter alia, dead, discarded or detached plants and their parts. Dead phytomass includes, for example, broken or torn leaves, axillary shoots, twigs, branches, fallen leaves, felled or pruned trees, as well as seeds, fruits and parts derived therefrom, as well as sawdust, wood chips and other products derived from wood processing.

[0067] The carbon content mentioned above is typically achieved by fillers based on the decomposition of biomass and can be determined by elemental analysis in accordance with DIN 51732:2014-7.

[0068] Preferably, the filler F1 has an oxygen content in the range of 15% to 30% by weight, preferably 17% to 28% by weight, particularly preferably 20% to 25% by weight, based on the ash- and moisture-free filler, where the oxygen content is defined herein as the difference with respect to the carbon, hydrogen, nitrogen and sulfur contents.

[0069] In addition, fillers F1 of the type defined above have acidic hydroxyl groups on the surface (so-called surface-available acidic hydroxyl groups). The measurement of the surface-available acidic hydroxyl groups can be carried out qualitatively and quantitatively by the colorimetric method of Sipponen. The method of Sipponen is based on the adsorption of the alkaline dye Azure B to the acidic hydroxyl groups available on the filler surface. Surface-available acidic hydroxyl groups are present in the sense of the present invention if there is a corresponding adsorption under the conditions mentioned in item 2.9 (p. 82) of the article below. Further details can be obtained from the article "Determination of surface-accessible acidic hydroxyls and surface area of ​​lignin by cation dye adsorption" (Bioresource Technology 169 (2014) 80-87). In the quantitative measurement, the amount of surface-available acidic hydroxyl groups is given in mmol / g filler. Preferably, the amount of surface available acidic hydroxy groups is in the range of 0.05 mmol / g to 40 mmol / g, particularly preferably 0.1 mmol / g to 30 mmol / g, more preferably 0.15 to 30 mmol / g. Preferred surface available acidic hydroxy groups are phenolic hydroxy groups.

[0070] There are also clear differences between the biomass-based fillers in terms of the BET surface (total specific surface area according to Brunauer, Emmett and Teller) and external surface (STSA surface area; statistical thickness surface area).

[0071] For example, WO 2017 / 085278A1 describes a filler containing hydrothermally treated lignin, i.e., lignin obtained by hydrothermal treatment, which is mainly composed of dead phytomass, and which is 5 to 200 m 2 / g range. In the experimental section of this publication, the STSA surface area is only 2.6 m 2 Even one of / g is mentioned.

[0072] In the context of the present invention, particular mention is also made of the term weighted arithmetic mean of the STSA surface of the filler. The term "weighted arithmetic mean" is used in its usual sense in the context of the present invention.

[0073] With regard to the STSA surface area with respect to filler F1, if only one filler F1 is used, its relative frequency is 1, so the weighted arithmetic mean of the STSA surface area of ​​this filler therefore corresponds exactly to the STSA surface area of ​​this filler F1 (weighted arithmetic mean of the STSA surface area = [STSA surface area of ​​F1] x 1). If a mixture of for example two different fillers F1' and F1'' is used, which contains for example 70% by weight of filler F1' (corresponding to a relative frequency of 0.7) and 30% by weight of filler F1'' (corresponding to a relative frequency of 0.3), the weighted arithmetic mean of the STSA surface area of ​​filler F1 = ([STSA surface area of ​​F1'] x 0.7) + ([STSA surface area of ​​F1''] x 0.3), or in general the weighted arithmetic mean of the STSA surface area of ​​filler F1 = Σ(STSA F1i ×h i ) (where STSA F1i represents the STSA surface area of ​​filler F1i, and h i represents the relative amount of this filler).

[0074] Preferably, the STSA surface area of ​​each filler F1 is also 40 to 80 m 2 / g, particularly preferably 40 to 75 m 2 / g, more preferably 42 to 70m 2 / g. Of course, the selection of the individual fillers F1 is based on the weighted arithmetic mean of the STSA surface area of ​​the filler F1 being in the range of 40 m 2 / g~80m 2 / g, preferably 42m 2 / g~75m 2 / g, particularly preferably 44m 2 / g~70m 2 / g.

[0075] Filler F1 has a volume-based median Dv(50) of particle size distribution of 0.5 μm to 5 μm, and a volume-based Dv(97) of particle size distribution of 3 μm to 23 μm. The volume-based median Dv(50) of particle size distribution is in the range of 0.5 to 5 μm, particularly preferably in the range of 1 to 4 μm, and more preferably in the range of 1 to 3 μm. The volume-based Dv(97) of particle size distribution is in the range of 3 μm to 23 μm, preferably up to 18 μm, particularly preferably up to 15 μm, more preferably up to 12 μm, even more preferably up to 10 μm, even more preferably up to 9 μm, even more preferably up to 8 μm, most preferably up to 7 μm, and more preferably up to 6 μm. The particle size distribution and the Dv(50) or Dv(97) value are measured by a laser diffraction method as described in detail in the experimental section. The Dv(97) value of the filler F1 is, of course, always greater than the Dv(50) value of the same filler F1.

[0076] The particle size distribution is not an inherent property resulting directly from the production of filler F1. Rather, the biomass-based filler is deagglomerated by a crushing process such as grinding to an extent that the particle size distribution according to the present invention is obtained. If the particle size of the filler particles is too large, the reinforcement is low, which is reflected in a flat tensile strain curve and a low tensile strength. If the particle size is too small, the dispersion in the polymer matrix becomes difficult and the filler particles will exist as poorly dispersed clusters.

[0077] Filler F1 14All the above ranges characterizing in terms of C content, carbon and oxygen content, STSA surface area and surface available acid groups, as well as particle size distribution, apply equally to all fillers F1 used according to the invention, but preferably to lignin-based fillers that represent the class of fillers preferred herein that can be produced from phytomass.

[0078] Rothemeyer and Sommer in their textbook "Kautschuk Technologie - Werkstoffe Verarbeitung Produkte" (3rd revised and expanded edition, 2013, pages 1196-1197) classify the various rubbers into three groups: low polarity and high swelling in oil, medium polarity and medium swelling in oil, and high polarity and low swelling in oil. Halobutyl rubbers are low polarity, despite their high reactivity.

[0079] Particularly surprising therefore is the good compatibility of the fillers F1 used according to the invention, in particular the lignin-based fillers, with the halobutyl rubber, which has a low polarity, since the fillers used according to the invention have a higher polarity compared to typical technical carbon blacks (this is due, among other things, to the content of surface-available acidic hydroxyl groups), although the higher oxygen content compared to technical carbon blacks also contributes to the compatibility.

[0080] Among the lignin-based fillers F1, hydrothermally treated lignin-containing phytomass is particularly preferred. A preferred treatment is hydrothermal treatment at temperatures between 150 ° C and 250 ° C in the presence of liquid water. Compared to the original lignin, the carbon content is usually increased and the oxygen content is decreased. Suitable methods for the treatment are described, for example, in WO 2017 / 085278 A1. Lignin-based fillers obtained by hydrothermal treatment are also referred to below as HTT lignins ("hydrothermally treated lignins"). The term HTC lignins ("hydrothermally carbonized lignins") is also frequently used in the literature. Fillers referred to as HTC lignins also fall under the term HTT lignins. Hydrothermal treatment at temperatures between 150 ° C and 250 ° C in the presence of liquid water is also referred to below as hydrothermal treatment. The HTT lignins described below are preferred fillers F1 to be used in the context of the present invention.

[0081] In one embodiment, the rubber composition according to the invention comprises more than 45 phr, preferably at least 46 phr, particularly preferably from 48 to 80 phr, more preferably from 50 to 75 phr, in particular from 50 to 70 phr, of the filler F1 as defined above used according to the invention.

[0082] In a further embodiment, the rubber composition according to the invention comprises more than 35 phr, preferably at least 36 phr, particularly preferably from 38 to 80 phr, more preferably from 40 to 70 phr, in particular from 50 to 65 phr, of the filler F1 as defined above used according to the invention in combination with one or more technical carbon blacks F2, the weighted arithmetic mean of the STSA surface area of ​​which is greater than or equal to 55 m 2 / g~95m 2 In this embodiment, the total amount of the filler F1 and the industrial carbon black F2 in the filler component is preferably at least 40 phr, particularly preferably at least 43 phr to 80 phr, more preferably 46 to 70 phr, and particularly preferably 48 to 65 phr.

[0083] <HTTリグニン> HTT lignin is obtained by hydrothermal treatment of lignin-containing raw materials and corresponds to a particularly preferred filler F1 that can be used according to the invention. The properties of HTT lignin can vary in a wide range. For example, different HTT lignins differ in BET and STSA surface area, ash content, pH, heat loss, as well as density, particle size, amount of surface-available acidic hydroxyl groups and particle size distribution.

[0084] In the context of the present invention, the special HTT lignin as filler F1 used according to the present invention serves as a replacement for the carbon black normally contained in rubber compositions for innerliners. The preparation of HTT lignin usable according to the present invention is described, for example, in WO 2017 / 085278 A1. The filler F1 produced according to the present invention is crushed, in particular ground, until the required particle size distribution is obtained.

[0085] Although the abovementioned documents WO 2017 / 085278 A1 and WO 2017 / 194346 A1 generally refer to the use of HTT lignin as a possible replacement for carbon black in tires, it should not be concluded that the behavior of HTT lignin in normal rubber compositions is easily transferable to the special rubber compositions of the present invention containing the more reactive halobutyl rubber. This is particularly true for the use of HTT lignin in rubber compositions based on halobutyl rubber, since these compositions have completely different properties from normal rubber compositions and, due to the high reactivity of the halogen atoms, in particular the chlorine atoms and especially the bromine atoms, an interaction or even a reaction with the fillers that can be used according to the present invention, in particular the HTT lignin, which has a chemically different surface and composition compared to technical carbon black, must be expected. Due to the above-mentioned differences between industrial carbon black and the fillers used in the present invention, especially in terms of the presence of surface-available acidic hydroxyl groups, preferably phenolic hydroxyl groups, the incorporability of the filler and its compatibility with the rubber component in the rubber composition according to the present invention is surprisingly good, even without the use of compatibilizers, especially without the use of silane compounds. The resulting vulcanized products have surprisingly good performances, and even important properties such as extremely low gas permeability required for innerliners are improved.

[0086] Also, contrary to the teaching of WO 2020 / 202125 A1, significantly larger amounts of filler F1 with STSA surfaces in the above ranges can be used, in particular at least 55 m 2 It was also surprising that excellent results were achieved in combination with a commercial carbon black having a high STSA surface area of ​​1000 nm / g.

[0087] In order to realize this advantage, the present invention requires that the special filler F1 be selected according to the purpose. Among the fillers F1, HTT lignin has been proven to be particularly suitable, since it has excellent compatibility with other components of the rubber composition, and furthermore with the special vulcanization system described below, and in particular, it provides the desired gas barrier properties and reduces crack formation and crack growth.

[0088] The filler F1 used according to the invention, and in particular the HTT lignin used according to the invention, allows to adjust a good balance of different properties for use in innerliners. Thus, the filler F1 has good reinforcing properties, as expressed by the stress value and tear strength of the vulcanized rubber, high breaking elongation of the rubber, and also promotes good dispersion of the filler particles in the rubber. In particular, when the filler F1 is used in large amounts, the gas permeability of the vulcanized rubber is significantly reduced and crack growth is reduced.

[0089] To achieve this, the filler F1 used in the context of the present invention, preferably HTT lignin, must have a surface area of ​​40 to 100 m in addition to the STSA surface area indicated above. 2 / g, preferably 42 to 75 m 2 / g, particularly preferably 44 to 70m 2 It is advantageous for the material to also have a BET surface area in the range of 1 / g.

[0090] Preferably, the filler F1 used according to the invention, preferably HTT lignin, has a pH in the range from 7 to 10, particularly preferably in the range from 8 to 9.5.

[0091] It was also found that ash and heat loss only had a small effect, as long as their values ​​were not too high and the content of active ingredients was reduced too much.

[0092] The filler used herein, preferably HTT lignin, has the potential to completely replace carbon black in the production of rubber compositions, especially rubber compositions for the manufacture of innerliners, as shown in the experimental section of this application, but the filler F1 used herein has a significantly higher STSA surface area than the technical carbon blacks N660 and N772 commonly used in innerliners, which means that the preferred rubber composition according to the invention does not need to contain carbon black from fossil-based materials.

[0093] This makes it possible, inter alia, to produce innerliners for pneumatic tires that have a significantly lower mass, improved air retention, and improved crack resistance with reduced crack growth at the same dimensions as comparable innerliners obtained using carbon black. The improved air retention, in particular, allows the rolling resistance of the tire to be maintained at an optimum level over the long term, making it possible for vehicles equipped with said tires to be operated more economically.

[0094] However, it is also possible to replace only a portion of the carbon black from fossil sources with one or more of the fillers F1 that can be used according to the invention, preferably with HTT lignin. The F2 carbon black described below is particularly advantageous for this purpose, even though its STSA surface, in particular, far exceeds the specifications of the carbon blacks usually used for innerliners. This also opens up new fields of application for the technical carbon black F2.

[0095] Other components of the rubber composition Filler F2 (=Industrial Carbon Black F2) In addition to the above-mentioned essential filler F1 used according to the invention, preferably HTT lignin F1, the rubber composition may contain in the filler component a further filler F2 different from F1, i.e. technical carbon black having the above-mentioned specifications.

[0096] For the calculation of the weighted arithmetic mean of the STSA surface of technical carbon black F2 the same method is applied as described for filler F1.

[0097] The weighted arithmetic mean STSA surface area of ​​technical carbon black F2 is 55m 2 / g~95m 2 / g range, preferably 60m 2 / g~92m 2 / g, particularly preferably 65m 2 / g~91m 2 / g range, more specifically 70m 2 / g~85m 2 / g range, especially 72m 2 / g~80m 2 / g range.

[0098] Preferably, the STSA surface area of ​​each technical carbon black F2 (i.e., filler F2) is also between 55 and 95 m 2 / g, particularly preferably 65 to 90m 2 / g, more preferably 70 to 85 m 2 / g. Of course, the selection of the individual fillers F2 is based on the essential requirement that the weighted arithmetic mean of the STSA surface area of ​​the fillers F2 be in the range stated in the previous paragraph.

[0099] Surprisingly, the use of the technical carbon black F2 characterized above has been found to be advantageous in terms of higher tensile strength, especially higher elongation at break. In particular, the smaller aggregate size seems to have a positive effect on crack growth, since, presumably, more particles in the same unit volume, and therefore more imperfections, oppose crack growth.

[0100] STSA surface area is 34m 2 / g and 28m 2 In comparison with the partial replacement of filler F1 by carbon blacks N660 and N772 used in the manufacture of innerliners, which have a carbon content of 55 to 95 m / g, the technical carbon black F2 characterized above has a carbon content of 55 to 95 m / g.2 / g, particularly preferably 65 to 90m 2 / g, more preferably 70 to 85 m 2 This allows for STSA surface areas in the range of 1 / g.

[0101] For example, carbon black N326 contains smaller aggregates due to its larger specific surface area (STSA) compared to semi-activated carbon blacks N660 and N772. The inventors of the present invention hypothesize that there are more particles in a unit volume of the same loading, which improves the physical interaction and results in a higher reinforcing effect. This appears to be particularly advantageous in terms of dynamic crack resistance.

[0102] Preferred technical carbon blacks F2 are described in the ASTM D1765 standard and have the designation N3XX. In particular, mention may be made of the technical carbon blacks of the designations N326, N330, N347, N339, N375 and N351.

[0103] Filler F2 is never used alone, but always in combination with at least filler F1 in the filler component, provided that, when filler F2 is used, the amount of filler F1 is more than 35 phr, preferably at least 36 phr, particularly preferably at least 38 phr, for example at least 40 phr.

[0104] When a further filler F2 having the above-mentioned properties is used, its content is preferably less than 25 phr, more preferably from 1 to 25 phr, more preferably from 5 to 20 phr, more preferably from 8 to 18 phr.

[0105] Preferably, the sum of the amounts of filler F1 and technical carbon black F2 is at least 45 phr, more preferably between 45 and 80 phr, more preferably between 45 and 70 phr, even more preferably between 45 and 60 phr.

[0106] The content of the filler F1 in the total of all the fillers F1+F2 is preferably 50 to 100 mass %, more preferably 65 to 100 mass %, and more preferably 80 to 100 mass %.

[0107] The weighted arithmetic mean of the STSA surface area of ​​the filler F1 and the technical carbon black F2 combined is at least 40 m 2 / g, particularly preferably 45m 2 / g~65m 2 / g, more preferably 47m 2 / g~63m 2 / g, more preferably 50m 2 / g~60m 2 / g.

[0108] <Filler F3> In addition to the filler F1 and the optionally present filler / technical carbon black F2, the rubber composition of the present invention may also contain further fillers F3 that do not fall within the definition of fillers F1 and F2. These fillers are in particular inorganic fillers with different particle sizes, particle surface areas and chemical properties, which can have different possibilities for influencing the vulcanization behavior. If further fillers are included, they should preferably have properties as similar as possible to the fillers F1 and F2 used in the rubber composition according to the present invention.

[0109] If other fillers F3 are used, these are preferably clay minerals, phyllosilicates such as talc; carbonates such as calcium carbonate; and silicates such as calcium, magnesium and aluminium silicates. However, these fillers may also be used in amounts of 40 ml each. 2 / g or less than 80m 2 / g STSA surface area, 14 Filler F3 may be filler F1 which meets the specifications for C content and carbon content and preferably also for particle size distribution and acidic hydroxyl groups. 2 / g or less than 95m 2The carbon black may be a technical carbon black F3 having a STSA surface area of ​​more than 100 nm / g.

[0110] Inorganic fillers, preferably silica and other fillers having Si-OH groups on the surface, may also be surface-treated. In particular, chlorination with organic silanes, such as alkylalkoxysilanes, aminoalkylalkoxysilanes, mercaptoalkylalkoxysilanes, etc., may be advantageous. Alkoxysilane groups can be bonded, for example, to the surface of silicates or silicas, or to other suitable groups, by hydrolytic condensation, while amino and thiol groups can react, for example, with halogenated, especially brominated, isoprene units of halobutyl rubber. This can cause mechanical reinforcement of the vulcanized rubber composition of the present invention.

[0111] The use of chlorinated fillers can hasten the attainment of the final vulcanized state and improve edge tear resistance.

[0112] The fillers may be used alone or in combination.

[0113] Preferably, in addition to the fillers F1 used according to the invention, in particular HTT lignin F1, and optionally any further fillers F2, no fillers F3 are used or only in small amounts. If further fillers F3 are used, these are preferably technical carbon blacks F3 not falling within the definition of technical carbon black F2, or clay minerals, for example phyllosilicates such as talc. The content of fillers F3 in the filler component is preferably less than 40 phr, particularly preferably 0 to 25 phr, more preferably 0 to 15 phr.

[0114] <Softener> The use of a softener can affect the properties of an unvulcanized rubber composition, particularly its processability, but can also affect the properties of a vulcanized rubber composition, particularly its flexibility at low temperatures.

[0115] Particularly suitable softeners in the context of the present invention are mineral oils from the group of paraffinic oils (substantially saturated linear hydrocarbons) and naphthenic oils (substantially saturated cyclic hydrocarbons). The use of aromatic hydrocarbon oils is also possible, but is less advantageous due to their poor dissolution behavior with halobutyl rubber. However, with regard to the adhesion of the rubber composition to other rubber-containing components in the tire, such as the carcass, a mixture of paraffinic and / or naphthenic oils may be advantageous as softeners.

[0116] Other softeners are, for example, esters of aliphatic dicarboxylic acids, such as adipic or sebacic acid, paraffin waxes, polyethylene waxes.

[0117] Among the softeners, paraffinic and naphthenic oils are particularly suitable in the context of the present invention.

[0118] Preferably, softeners, particularly preferably paraffinic oils and / or naphthenic oils, are used in an amount of 0 to 20 phr, preferably 5 to 15 phr, particularly preferably 7 to 13 phr.

[0119] <Adhesion enhancing resin ("tackifying resin")> So-called adhesion enhancing resins can be used to improve the adhesion between the vulcanized rubber compounds of this invention and other adjacent tire components.

[0120] Particularly suitable resins are phenol-based resins, preferably from the group consisting of phenolic resins, phenol-formaldehyde resins and phenol-acetylene resins.

[0121] In addition to phenol-based resins, aliphatic hydrocarbon resins such as Escorez™ 1102RM from Exxon Mobil, and aromatic hydrocarbon resins can also be used. Aliphatic hydrocarbon resins, in particular, improve adhesion to other rubber components of the tire. Aliphatic hydrocarbon resins generally have lower adhesion than phenol-based resins and can be used alone or in mixtures with phenol-based resins.

[0122] If any adhesion enhancing resins are used, they are preferably selected from the group consisting of phenol-based resins, aromatic hydrocarbon resins and aliphatic hydrocarbon resins, preferably in an amount of 0-15 phr or 1-15 phr, particularly preferably 2-10 phr, more preferably 3-8 phr.

[0123] <Additives that accelerate vulcanization> The rubber composition according to the present invention may also contain additives that accelerate vulcanization but cannot initiate vulcanization by themselves. Such additives include vulcanization accelerators such as saturated fatty acids having 12 to 24, preferably 14 to 20, particularly preferably 16 to 18 carbon atoms, e.g. stearic acid, and zinc salts of the aforementioned fatty acids. Thiazoles may also belong to these additives. However, it is also possible to use vulcanization accelerator additives only in the vulcanization system described below.

[0124] When a vulcanization accelerator additive, in particular the above-mentioned fatty acids and / or zinc salts thereof, preferably stearic acid and / or zinc stearate, is used in the rubber composition according to the present invention, the amount thereof is preferably 0 to 5 phr, particularly preferably 0.5 to 3 phr, particularly preferably 1 to 2 phr.

[0125] Preferably, the rubber composition according to the invention therefore contains, in addition to the constituents necessarily used, i. Rubbers other than halobutyl rubbers; ii. technical carbon black F2 and / or fillers F3; iii. softeners; iv. Adhesion enhancing resins, and v. Additives that accelerate vulcanization The composition contains one or more components selected from the group consisting of:

[0126] If one or more of the components listed in items i. to v. above are included, i. is preferably a rubber selected from the group consisting of natural rubber, butyl rubber, and styrene butadiene rubber; ii. is a filler F2 as defined above or a filler F3 different from F2 and selected from the group of carbon blacks and phyllosilicates, iii. is preferably an ester of an aliphatic dicarboxylic acid, a paraffinic oil and / or a naphthenic oil; iv. is a resin selected from the group consisting of aliphatic hydrocarbon resins, aromatic hydrocarbon resins, phenolic resins, phenol-formaldehyde resins, and phenol-acetylene resins; v. is an additive selected from the group of saturated fatty acids having 12 to 24 carbon atoms and the group of thiazoles.

[0127] When components i. to v. are included, they are preferably included in the following amounts: i. 0 to 40 phr, particularly preferably 0 to 30 phr, more preferably 0 to 20 phr or 0 phr; ii. 0 to 40 phr, more preferably 0 to 25 phr, particularly preferably 0.1 to 20 phr, more preferably 0.5 to 18 phr; iii. 0 to 20 phr, particularly preferably 5 to 15 phr, more preferably 7 to 13 phr; iv. 0 to 15 phr, particularly preferably 2 to 10 phr, more preferably 3 to 8 phr; v. 0 to 5 phr, particularly preferably 0.5 to 3 phr, more preferably 1 to 2 phr.

[0128] <Vulcanizable rubber composition> The vulcanizable rubber composition of the present invention comprises a rubber composition according to the present invention and a vulcanization system which serves to vulcanize the composition.

[0129] Vulcanization System The vulcanization system is not included in the rubber composition of the present invention, but is treated herein as an additional system that controls the crosslinking of said composition. By adding the vulcanization system to the rubber composition according to the present invention, a vulcanizable rubber composition also according to the present invention is obtained.

[0130] A wide variety of different vulcanization systems can be used with the rubber compositions of the present invention based on halobutyl rubbers. The weaker chlorine-carbon and especially bromine-carbon bonds compared to carbon-carbon bonds allow for faster vulcanization as well as better co-vulcanization with general-purpose rubbers.

[0131] The vulcanization of the rubber composition of the present invention is preferably carried out using zinc oxide and / or sulfur.

[0132] In the preferred variants described below, zinc oxide is preferably used in combination with different organic compounds for vulcanization. Different additives can influence the vulcanization behavior and the properties of the vulcanized rubber thus obtained.

[0133] In a first variant of vulcanization based on zinc oxide, it is preferable to add small amounts of saturated fatty acids having 12 to 24, preferably 14 to 20, particularly preferably 16 to 18 carbon atoms, such as stearic acid and / or zinc stearate, as vulcanization accelerators to the zinc oxide. This allows the vulcanization rate to increase. However, in most cases the use of said fatty acids leads to a decrease in the final grade of the vulcanization.

[0134] In a second variant of vulcanization based on zinc oxide, so-called thiurams, such as thiuram monosulfides, thiuram disulfides and / or dithiocarbamates, are added to the zinc oxide in the absence of sulfur in order to reduce the scorch time and, in particular, to form a stable network and thus improve the efficiency of the vulcanization.

[0135] In a third variant of vulcanization based on zinc oxide, alkylphenol disulfides are added to the zinc oxide to adjust and in particular accelerate the scorch time.

[0136] Another, or fourth, variant of the zinc oxide-based vulcanization uses a combination of zinc oxide with polymethylolphenolic resins and their halogenated derivatives, without the use of sulfur or sulfur-containing compounds.

[0137] In a further fifth variant of the vulcanization based on zinc oxide, the vulcanization is carried out by a combination of zinc oxide with thiazoles and / or sulfenamides, preferably with sulfur. The thiazoles and sulfenamides are preferably selected from the group consisting of 2-mercaptobenzothiazole (MBT), mercaptobenzothiazyl disulfide (MBTS), N-cyclohexyl-2-benzothiazylsulfenamide (CBS), 2-morpholino-thiobenzothiazole (MBS) and N-tert-butyl-2-benzothiazylsulfenamide (TBBS). The addition of sulfur to such a system increases both the vulcanization rate and the vulcanization range, contributing to the processability of the rubber composition in the vulcanization process. Co-vulcanization with rubbers different from halobutyl rubber, in particular with the above-mentioned rubbers, is also preferred. The use of this vulcanization system preferably results in a heat- and fatigue-resistant vulcanizate that, even in the vulcanized state, exhibits good adhesion to the rubber compositions of other components of the vehicle tire, in particular the carcass. A particularly advantageous vulcanization system comprises zinc oxide, a thiazole, preferably mercaptobenzothiazyl disulfide (MBTS), and sulfur. Particularly preferred is the combination of the first and fifth variants, i.e. the use of a vulcanization system comprising zinc oxide, a thiazole, preferably mercaptobenzothiazyl disulfide (MBTS), sulfur, and stearic acid and / or optionally zinc stearate.

[0138] Less preferred vulcanization systems are based on pure sulfur vulcanization or peroxide vulcanization, the latter of which can result in an undesirable reduction in molecular weight due to molecular cleavage, especially when butyl or other rubbers are also used.

[0139] In the context of the present invention, the vulcanization of the rubber composition according to the invention is carried out in the presence of a specific filler F1, preferably a specific HTT lignin, and optionally technical carbon black F2. The excellent properties of the vulcanized rubber composition according to the invention, in particular its suitability as an innerliner, are essentially based on the combination of a suitable rubber component with specific amounts of a specific filler F1, particularly preferred HTT lignin F1, and optionally F2, and a vulcanization system based on zinc oxide. The vulcanization system is preferably that of the variant mentioned above as the fifth variant, more preferably a combination of the first and fifth variants.

[0140] Components of the vulcanization system that cannot initiate vulcanization by themselves may also be included in the rubber composition of the present invention as "other components of the rubber composition". Thus, it is possible that in particular stearic acid and / or optionally zinc stearate and / or a thiazole compound are already present in the rubber composition and that a complete vulcanization system is formed in situ by adding zinc oxide and sulfur.

[0141] <Kit of parts> Due to the relationship between the rubber composition according to the invention and the crosslinking system selected for its vulcanization, the invention also relates to a kit-of-parts comprising the rubber composition according to the invention and a vulcanization system, preferably based on zinc oxide and / or sulfur. In the kit-of-parts, the rubber composition according to the invention and the vulcanization system are spatially separated from each other and can therefore be stored. The kit-of-parts serves for the preparation of a vulcanizable rubber composition. For example, the rubber composition according to the invention, constituting one component of the kit-of-parts, can be used as component (A) in step 1 of the below-described method for preparing a vulcanizable rubber compound, and the second component of the kit-of-parts, i.e. the vulcanization system, can be used as component (B) in step 2 of said method.

[0142] Preferably, the kit of parts comprises: As component (A), a rubber composition according to the present invention, and As component (B), a vulcanization system containing zinc oxide and / or sulfur Includes.

[0143] Particularly preferably, the kit of parts comprises As component (A), a rubber composition according to the present invention, and As component (B), a vulcanization system comprising zinc oxide, sulfur and thiazoles; or A rubber composition according to the present invention containing thiazoles as component (A), and As component (B), a vulcanization system containing zinc oxide and / or sulfur Includes.

[0144] More preferably, the kit-of-parts comprises: As component (A), a rubber composition according to the present invention, and as component (B), a vulcanization system comprising zinc oxide, sulfur, thiazoles, stearic acid, and optionally zinc stearate; or A rubber composition according to the invention, which contains as component (A) stearic acid and, optionally, zinc stearate, and As component (B), a vulcanization system comprising zinc oxide, sulfur and thiazoles. Includes.

[0145] The preferred thiazole in the kit-of-parts is MBTS.

[0146] In contrast to a vulcanizable rubber composition, which already contains both the components of the rubber composition according to the invention and the components of the accompanying vulcanization system in a homogeneous mixture so that the vulcanizable rubber composition can be directly vulcanized, in a kit of parts the rubber composition according to the invention and the vulcanization system are spatially separated.

[0147] In this specification, the vulcanizable rubber composition obtainable from the kit-of-parts is also called "green compound". This vulcanizable rubber composition can be obtained by a two-stage process described in the following section.

[0148] <Method for preparing the rubber composition according to the present invention and the vulcanizable rubber composition obtained from said composition> The preparation of the vulcanizable rubber compound is preferably carried out in two stages.

[0149] In a first step, the rubber composition according to the present invention is first prepared as a base compound (masterbatch) by compounding the components of the rubber composition. In a second step, the components of the vulcanization system are mixed.

[0150] Phase 1 Preferably, halobutyl rubber and optionally any additional rubbers, as well as optionally any adhesion enhancing resins, are provided. However, the latter can also be added together with other additives. Preferably, the rubber is used at least at room temperature (23° C.) or after preheating to a temperature below 50° C., preferably below 45° C., particularly preferably below 40° C. Particularly preferably, the rubber is pre-masticated for a short time before adding the other components. If an inhibitor such as magnesium oxide is used for subsequent vulcanization control, it is preferably added at this point as well.

[0151] Thereafter, the filler F1 used according to the invention, preferably as HTT lignin, and optionally other fillers F2 and / or F3, is added, preferably excluding zinc oxide, since zinc oxide is used in the rubber composition according to the invention as a constituent of the vulcanization system and is therefore not considered a filler here. The addition of the filler F1 used according to the invention, preferably as HTT lignin, and optionally other fillers F2 and / or F3, is preferably carried out stepwise.

[0152] Advantageously, but not necessarily, the softener and other components such as stearic acid and / or zinc stearate are added only after the addition of the filler F1 used according to the invention, preferably HTT lignin, or other fillers F2 and / or F3, if used. This facilitates the incorporation of the filler F1 used according to the invention, preferably HTT lignin, and other fillers F2 and / or F3, if included. However, it may be advantageous to incorporate part of the filler F1 used according to the invention, preferably HTT lignin, and other fillers F2 and / or F3, if included, together with the softener and optionally any other components optionally used.

[0153] The maximum temperature obtained during the preparation of the rubber composition in the first stage ("dump temperature") should not exceed 140°C, since above this temperature there is a risk of partial decomposition of the reactive halobutyl rubber. Preferably, the maximum temperature during the preparation of the rubber composition in the first stage is between 100°C and 130°C, particularly preferably between 105°C and 120°C.

[0154] Mixing of the components of the rubber composition according to the invention is usually carried out by means of an internal mixer equipped with tangential or mesh (i.e. intermeshing) rotors, the latter usually allowing better temperature control, however mixing can also be carried out using, for example, a double roll mixer.

[0155] After preparation of the rubber composition, it is preferred to cool it before carrying out the second stage. This type of process is also called maturation. Typical maturation times are 6 to 24 hours, preferably 12 to 24 hours.

[0156] Second Phase In a second step, the components of a vulcanization system are incorporated into the rubber composition of the first step to obtain a vulcanizable rubber composition according to the present invention.

[0157] If a vulcanization system based on zinc oxide is used as the vulcanization system, the zinc oxide and other components, especially sulfur, particularly preferably thiazoles, are added in a second stage.

[0158] The maximum temperature obtained during the preparation of the compound with the vulcanization system in the second stage ("dump temperature") should preferably not exceed 110°C, particularly preferably not exceed 105°C. The preferred temperature range is 90°C to 110°C, particularly preferably 95°C to 105°C. At temperatures above 105°C to 110°C, premature vulcanization may occur.

[0159] After incorporating the vulcanization system in the second stage, the composition is preferably cooled.

[0160] In the above two-stage process, the rubber composition according to the present invention is obtained in the first stage and is replenished in the second stage to form a vulcanizable rubber composition, particularly a vulcanizable rubber composition for an innerliner.

[0161] <Method for Further Processing the Vulcanizable Rubber Composition According to the Present Invention> The vulcanizable rubber composition obtained by the above-mentioned two-stage process is preferably further processed in a calendaring, extrusion, or roller head process.

[0162] Calendar processing The vulcanizable rubber composition of the present invention is preferably fed to a calender in a first step (a), for example using a preheating mill and a downstream feeder mill, or fed in an extrusion process using an extruder. In either case, the vulcanizable rubber composition should have a temperature of preferably 65°C to 85°C, particularly preferably 70°C to 80°C, before being fed to the calender.

[0163] In the second step (b), a calendering is carried out, where different roller positions of preferably three or four rollers in the calender are possible. Preferably, the calendering is carried out by a four-roll Z-calender ("oblique Z-calender") or a four-roll L-calender ("inverted L-calender"). Herein, the cold side pick-up roll preferably has a temperature of 75°C to 85°C, while the hot side roll preferably has a temperature of 85°C to 95°C.

[0164] After calendering, the calendered vulcanizable rubber composition leaves the calender in a third step (c) as a calendered web, which is cooled, preferably to a temperature below 35° C., before further processing. As the calendered web leaves the calender, it is also possible to consolidate several calendered webs into multiple layers. Care must be taken to avoid undesirable air entrapment during the bonding process.

[0165] After these three steps, in a fourth step (d), the calendered web, or the multi-layer bonded calendered web, is advantageously stored for at least 3 hours, more preferably at least 4 hours, preferably at least 12 to 24 hours, which serves to completely cool the calendered web and relieve stress.

[0166] The calendering is carried out at a calendering speed in the range of preferably 20 to 35 m / min, particularly preferably 25 to 30 m / min.

[0167] Extrusion Besides calendaring, it is also possible to obtain the innerliner by extrusion.

[0168] The feeding of the vulcanizable rubber composition of the present invention to the extruder is preferably carried out in a first step (a), for example via a double roll mixer or other suitable feeding device, whereby the vulcanizable rubber composition should preferably have a temperature of 65°C to 85°C, particularly preferably 70°C to 80°C, before being fed to the calender.

[0169] In the second step (b) extrusion, temperatures of 100° C. can be obtained, therefore special care must be taken to avoid scorching.

[0170] After extrusion, the extruded vulcanizable rubber composition leaves the extruder in a third step (c) as a web, which is cooled, preferably to a temperature below 35° C., before further processing. As the web leaves the extruder, multiple webs can also be bonded together in multiple layers. Care must be taken to avoid undesirable air entrapment during the bonding process.

[0171] After these three steps, in a fourth step (d), it is advantageous to store the web, or the multi-layer bonded web, for at least 3 hours, more preferably at least 4 hours, and preferably at least 12 to 24 hours, which serves to thoroughly cool the web and relieve stress.

[0172] Roller Head Process In the roller head process, in contrast to the above-mentioned calendaring process using multiple rollers, the rubber compound is fed from an extruder with a preform head into the calendar nip of a two-roll or three-roll calendaring machine. The extruder itself can be fed with warm or cold feedstock. For example, it is also possible to use a cold-fed pin extruder. The roller nip (calender nip) can be optimally fed if the compound fed is adapted to the thickness and width of the web to be calendared, which can be achieved by the choice of the preform head and the exchangeable forming die attached to its tip.

[0173] The roller head line is intermediate in terms of operation between the extruder and the calender; whereas uniform flow in the extruder die is crucial to the quality and dimensions in the production of thick webs, the calendering action is more important in the production of thin webs.

[0174] Operating temperatures are within the ranges of these processes described above for calendering and extrusion.

[0175] As already mentioned in connection with calendering, the finished web must be cooled after leaving the calender in accordance with step (c) above, preferably followed by step (d) above.

[0176] The vulcanizable webs obtained by calendering, extrusion or roller head processes have a layer thickness of 0.3 to 5 mm, particularly preferably 0.4 to 4 mm, more preferably 0.5 to 3 mm. These layer thickness ranges are typical for innerliners.

[0177] <Vulcanized rubber composition> An object of the invention is also a vulcanized rubber composition obtainable from the vulcanizable rubber composition described above, for example also by using a kit-of-parts.

[0178] The vulcanization conditions depend on the vulcanization system used. The suitable vulcanization temperature is preferably 140°C to 200°C, particularly preferably 150°C to 180°C.

[0179] Preferably, the vulcanized rubber composition is an innerliner for a pneumatic tire.

[0180] Properties of vulcanized rubber compositions The vulcanized rubber composition obtained from the vulcanizable rubber composition according to the present invention is preferably (a) a Shore A hardness in the range of 35 to 65, particularly preferably 38 to 60, and more preferably 40 to 55; and / or (b) a 300% modulus of 2.8 MPa to 8 Pa, particularly preferably 3.0 MPa to 6.0 MPa, and more preferably 3.0 MPa to 4.0 MPa; and / or (c) 1.000 g / cm 3 ~1.120g / cm 3 , particularly preferably 1.010 g / cm 3 ~1.100g / cm 3 , more preferably 1.020 g / cm 3 ~1.080g / cm 3 density; and / or (d) 3.8 × 10 -17 m 2 / Pas, particularly preferably 2.5×10 -17 m 2 / Pas~3.8×10 -17 m 2 / Pas, more preferably 2.7×10 -17 m 2 / Pas~3.7×10 -17 m 2 / Pas, e.g. 2.8×10 -17 m 2 / Pas~3.5×10 -17 m 2 Gas permeability of / Pas has.

[0181] In general, a higher content of the filler F1, particularly HTT lignin, and optionally other fillers that can be used according to the invention, typically leads to a further decrease in gas permeability, but at the expense of the tear strength and elongation at break of the compound. By partially replacing the filler F1 with technical carbon black F2, both the tensile strength and the elongation at break can be significantly improved, without a significant deterioration in the other properties.

[0182] <Method for producing a pneumatic tire having an inner liner made from the vulcanizable rubber composition according to the present invention> The vulcanizable web obtainable by the above process is preferably stored in the form of a roll until use and serves as the material for the innerliner in the manufacture of pneumatic tires. For this purpose, the web must be cut to the circumference of a drum, which can be done by using ultrasonic knives or heatable rotating circular knives, the latter being preferably used in the so-called roll-on-and-cut process.

[0183] The innerliner is typically vulcanized under pressure and / or heat along with the tire carcass and / or other tire components.

[0184] The suitable vulcanization temperature is preferably 140°C to 200°C, particularly preferably 150°C to 180°C.

[0185] The process can be carried out, for example, in such a way that the tire blank is molded into the closing mound by closing the press. For this purpose, the inner bellows (heated bellows) can be pressurized with low pressure (less than 0.2 bar) so that the bellows also fits into the tire blank. The press, and therefore the mound, is then completely closed. The pressure in the bellows increases (usually up to a molding pressure of about 1.8 bar). This results in the imprinting of the profile in the tread, as well as the labeling of the sidewall. The next processing step is to lock the press and apply a clamping force. The clamping force depends on the type of press and the tire size, and can reach 2500 kN when using hydraulic cylinders. After the clamping force has been applied, the actual vulcanization process begins. Here, the mold is continuously heated from the outside with steam, the temperature is usually set between 150 and 180 ° C. There are variants of the internal medium that vary widely depending on the type of tire. For example, steam or hot water is used inside the heated bellows. The internal pressure can vary depending on the type of tire, for example for passenger cars or trucks.

[0186] All measured quantities mentioned herein in connection with the present invention are measured according to the procedures mentioned in the experimental section.

[0187] <Use of the filler F1 used according to the invention, in particular HTT lignin F1 and mixtures of F1 and F2> Another object of the present application is the use of a filler F1, preferably HTT lignin, as defined above in relation to the rubber composition according to the invention, or a mixture of a filler F1, also defined above, with technical carbon black F2, in a rubber composition for an innerliner, wherein the filler F1 and the technical carbon black F2 are used in a total amount of at least 46 phr.

[0188] The above uses are intended to reduce in particular the gas permeability and crack growth, in particular compared to rubber compositions which contain technical carbon black N660 and / or technical carbon black N772 instead of F1 and / or F2. EXAMPLES

[0189] The components of the rubber composition, the unvulcanized rubber composition and the vulcanized rubber composition were subjected to various test procedures which are described in more detail below.

[0190] <Characteristics evaluation of fillers F1 and F2> Mass-related surfaces (BET and STSA surfaces) The specific surface area of ​​HTT lignin was measured by nitrogen adsorption according to the ASTM D 6556 (2019-01-01) standard for industrial carbon black, in which the BET surface area (total specific surface area according to Brunauer, Emmett and Teller) and external surface area (STSA surface area; statistical thickness surface area) were measured as follows:

[0191] Prior to the measurement, the samples to be analyzed were dried at 105°C to a dry matter content of 97.5% by mass or more. In addition, the measuring cell was dried in a drying oven at 105°C for several hours before the sample was weighed. The sample was then placed into the measuring cell using a funnel. If the upper measuring cell shaft became contaminated during filling, it was cleaned using a suitable brush or pipe cleaner. For strongly splashing (statically charged) materials, glass wool was added to the sample and weighed. This glass wool was used to hold any material that could splash and contaminate the unit during the bake-out process.

[0192] The samples to be analyzed were baked out at 150°C for 2 hours, while the standard Al2O3 was baked out at 350°C for 1 hour.

[0193] The following N2 loadings were used for the pressure range: p / p0=0~0.01:N2 addition amount:5ml / g p / p0=0.01~0.5:N2 addition amount:4ml / g To measure the BET, extrapolation was performed using at least six measurement points in the range of p / p0 = 0.05-0.3. To measure the STSA, extrapolation was performed using at least seven measurement points in the range of adsorbed N2 layer thickness t = 0.4-0.63 nm (corresponding to p / p0 = 0.2-0.5).

[0194] pH measurement The pH was measured according to the ASTM D 1512 standard described below. The dried samples, if not already in powder form, were ground or crushed to a powder. In each case, 5 g of sample and 50 g of fully deionized water were weighed into a glass beaker. The suspension was heated to 60°C with constant stirring using a magnetic stirrer with heating function and a stir bar, and the temperature was maintained at 60°C for 30 minutes. The heating function of the stirrer was then turned off and the mixture was cooled with stirring. After cooling, the evaporated water was replenished by adding fully deionized water again and stirred again for 5 minutes. The pH value of the suspension was measured with a measuring instrument. The temperature of the suspension should be 23°C (± 0.5°C). Duplicate measurements were performed for each sample and the average value was reported.

[0195] Bulk density measurement The bulk density of the samples was determined according to ISO 697 as described below. A standard beaker (volume 100 ml) according to DIN ISO 60 for bulk density measurements was placed in a dish to collect the overflow. Using a funnel and a shovel, the beaker was filled to overflowing. The excess was scraped off along the edge of the beaker with the straight edge of the shovel. The outside of the beaker was wiped with a dry cloth and weighed to an accuracy of 0.1 g.

[0196] Measurement of surface available acidic hydroxyl groups (OH group density) The determination of surface-accessible acidic hydroxyl groups was carried out qualitatively and quantitatively by the colorimetric method of Sipponen. The method by Sipponen is based on the adsorption of the alkaline dye AzureB to the acidic hydroxyl groups available on the filler surface and is described in detail in the paper "Determination of surface-accessible acidic hydroxyls and surface area of ​​lignin by cation dye adsorption" (Bioresource Technology 169 (2014) 80-87). The amount of surface-accessible acidic hydroxyl groups is given in mmol / g filler. Regardless of the method of obtaining the filler, this process was applied not only to lignin-based fillers but also, for example, to the comparative carbon black N660.

[0197] 14 Measurement of C content 14 The determination of the C content (content of biological carbon) can be carried out by the radiocarbon method according to DIN EN16640:2017-08.

[0198] Particle size distribution measurement The particle size distribution can be measured by laser diffraction of the material dispersed in water (1% by weight in water) according to ISO 13320:2009. The measurement is preceded by an ultrasonic treatment of 12000 Ws. The volume fraction is specified in μm, for example as Dv(97) (the diameter of the particles corresponding to 97% of the volume of the sample is less than this value). A similar method is applied for the Dv(50) value.

[0199] <Characteristics evaluation of vulcanizable rubber compositions ("green compounds")> Reaction rate / vulcanization rate measurement The reaction kinetics of the non-vulcanized rubber compounds ("green compounds") was measured by measuring the torque [dNm] over time according to DIN 53529Tl3 (torsional shear rotorless curemeter) using a rheometer MDR 3000 Professional (MonTech Werkstoffprufmaschinen GmbH, Buchen, Germany). The upper and lower rotor plates of the rheometer were heated to 160 °C. 5.5 g ± 0.5 g of the non-vulcanized rubber composition was cut out from the center of the sheet with scissors, taking care that the cut out area was square and that the diagonal of this area corresponded to the diameter of the rotor of the rheometer. Before placing the non-vulcanized rubber composition on the rotor of the rheometer, the top and bottom of the cut out area were covered with a film. After inserting the non-vulcanized sample, the measurement was started immediately.

[0200] Minimum torque (M L ) and maximum torque (M H ) and calculate the difference Δ(M H -M L ) was calculated.

[0201] Furthermore, for each measurement curve, the minimum torque M L Maximum torque M H is defined as 0% of the maximum torque M H was normalized to 100%. Then, the minimum torque M L Starting from the point, the torque reaches its maximum torque M H The time when the temperature reached 10%, 50%, and 90% of the T 10 , T 50 , T 90 It was decided.

[0202] <Evaluation of properties of vulcanized rubber composition> Shore A hardness measurement The Shore A hardness measurements of the vulcanized rubber compositions were carried out according to ISO 7619-1 using a digital Shore hardness tester from Sauter GmbH. Before each measurement, the instrument was calibrated using the included calibration plate. For the hardness measurements, three punched S2 bars were stacked on top of each other for tensile testing according to DIN 53504. Hardness measurements were carried out at five different positions on the stack. The Shore A hardness of the vulcanized rubber compositions corresponds to the average of the five measurements. Between vulcanization and testing, the samples were stored at room temperature in the laboratory for at least 16 hours.

[0203] Measurement of density of vulcanized rubber composition The density of the vulcanized rubber compositions was determined according to DIN EN ISO 1183-1:2018-04 (Determination of the density of non-cellular plastics) Method A (immersion method). Ethanol was used as the immersion medium. The density of the vulcanized rubber compositions corresponds to the average value of three determinations. Between vulcanization and testing, the samples were stored at room temperature in the laboratory for at least 16 hours.

[0204] Gas permeability measurement The determination of the gas permeability of the vulcanized rubber compositions to air was carried out according to ISO 15105. The measurements were carried out at 70 °C. The gas permeability corresponds to the average of three measurements. Between vulcanization and testing, the samples were stored at room temperature in the laboratory for at least 16 hours.

[0205] Measurement of compression set The compression set of the vulcanized rubber compositions was determined according to DIN ISO 815-1:2016-09. Three specimens were tested for each sample. The exposure time was 22 h, measured from the moment the specimens were placed in the heating cabinet. The test temperature was 70 °C. The applied compressive stress was 25% of the initial thickness of the specimen. The specimens were stored at room temperature for at least 16 h between vulcanization and testing.

[0206] Measurement of tear strength, tear elongation, and stress value (modulus) Tensile testing was used to measure the tear strength, tear elongation, and stress values ​​of non-preloaded specimens, in which a specimen is stretched at a constant strain rate until it tears, and the force and change in length required are recorded.

[0207] Tear strength: The tear strength σR is the quotient of the force FR measured at the moment of tearing and the initial cross-sectional area A0 of the sample body.

[0208] Tensile strength: The tensile strength σmax is the quotient of the maximum measured force Fmax and the initial cross-sectional area A0 of the sample body. For elastomers, the force FR occurring at tearing is generally also the maximum force Fmax.

[0209] Tearing elongation: The tearing elongation εR is the quotient of the change in length measured at the moment of tearing LR-L0 and the initially measured length L0 of the sample body. The tearing elongation is expressed as a percentage. In the sample bar used, L0 is the defined distance between the two measurement marks.

[0210] Stress value: The stress value σi is the tensile force Fi present when a certain elongation is reached and is related to the initial cross section A0. In the case of the sample bar, the strain is related to the initially measured length L0, i.e. the defined distance between the measurement marks.

[0211] The measurements of tensile strength, elongation at break and stress values ​​of the vulcanized rubber compositions were carried out in accordance with ISO 37 using a Gibitre Instruments Tensor Check type testing machine. Between vulcanization and testing, the samples were stored at room temperature in the laboratory for at least 16 hours. To measure the modulus, at least five dumbbell-shaped test samples were punched out of the vulcanized rubber compositions with the specimen dimensions described in ISO 37 (rod type S2). The thickness of the specimens was measured using a calibrated thickness gauge from Kafer Messuhren and corresponds to the average value of three measurements taken at different positions on the bridge. The crosshead speed during the tensile tests was 200 mm / min. The measurements given for tensile strength, elongation at break and stress values ​​(100, 200 and 300% modulus) are the average values ​​of five measurements.

[0212] De Mattia crack growth test according to DIN 53522 For the fatigue bending test to evaluate the resistance of elastomers to crack growth, a dynamic test is carried out using a De Mattia testing machine. The specimens (140 x 25 x 6.3 mm) have a transverse groove and are deformed in compression using an eccentric. The bending cycle is 300 times per minute, which causes the specimens to bend to 40% of the clamping length. The specimens are drilled in the center of the groove with a cutting tool as specified in the standard, which causes a 2 mm crack before the start of the test. The test is continued until there is a significant change in the crack length. The number of cycles is recorded until the crack has propagated to a certain size.

[0213] Volume swelling by toluene and M c Calculation A cross-linked polymer swells in a solvent (LM) to a certain equilibrium value that depends on the degree of cross-linking, which can be measured by the swelling elongation.

[0214] The swelling behavior of elastomers is governed by the average molecular network arc length M, one of the most important structural parameters of polymer networks. cThis parameter has a decisive influence on the mechanical properties of elastomers.

[0215] M c is obtained from the following relation: M c =A / B×q 5 / 3 M c = average molar mass between two crosslinking positions A = density of rubber x molar volume of solvent B=0.5-Flory-Huggins constant (here 0.35) q = swelling degree

[0216] The degree of swelling q corresponds to the reciprocal of the volume fraction q=1 / v2. The value v2 is calculated from the following formula: v2=1 / (1+V1 / V0), where V1 is the volume of the solvent and V0 is the volume of the unswollen rubber. The ratio V1 / V0 is calculated using the following formula: V1 / V0=(m q -m0) / ρ L / m0 / ρ m q = mass of inflated rubber m0 = mass of rubber before swelling ρ L = density of the solvent ρ = density of rubber

[0217] <Preparation Example> Preparation of HTT lignin usable according to the invention Three fillers F1A, F1B, and F1C derived from renewable raw materials could be characterized as shown in Table 1. The characterization results were compared with commercially available ASTM standard industrial carbon black types N660, N772, and N326.

[0218] Fillers F1A, F1B and F1C were prepared by hydrothermal treatment of lignin, as described in detail in WO 2017 / 085278 A1.

[0219] For this purpose, a lignin-containing liquid was prepared. First, water and lignin were mixed to prepare a lignin-containing liquid with a dry organic matter content of 15% by mass. The lignin was then largely dissolved in the lignin-containing liquid. For this purpose, NaOH was added to adjust the pH value. The preparation of the solution was assisted by strong mixing at 80 ° C for 3 hours. The lignin-containing liquid was then subjected to hydrothermal treatment to obtain a solid. The prepared solution was heated at 2 K / min to a reaction temperature of 220 ° C and maintained at this temperature for a reaction time of 8 hours. It was then cooled. As a result, an aqueous solid suspension was obtained. The solid was largely dehydrated and cleaned by filtration and washing. Subsequent drying and heat treatment were carried out in a fluidized bed under nitrogen. In the drying process, it was heated at 1.5 K / min to a temperature of 50 ° C and held for 2.5 hours, then for heat treatment it was heated at 1.5 K / min to a temperature of 190 ° C, held for 15 minutes and cooled again. The dried solid was deagglomerated in a counter jet mill using nitrogen to the Dv(97) value (measured according to the measurement method described above) and the particle size shown in Table 1.

[0220] [Table 1]

[0221] Preparation of different rubber compositions (first stage) Rubber compositions (base compounds; masterbatches) were prepared as follows using the components and amounts shown in Table 2 in a Haake Rheomix 3000S mixer equipped with Thermo Fischer Banbury rotors.

[0222] Before mixing started, the mixing chamber was heated to 40°C. The amount of each component was calculated to give a filling level of 70% in the mixing chamber. All components were pre-weighed on a Kern scale. After starting the rotor (50 rpm), the mixing chamber was loaded with rubber, the filling device leading to the mixing chamber was pneumatically locked, and mixing was carried out for a total mixing time of 1 min. The filling device of the mixing chamber was then opened, 1 / 3 of the filler amount and additives (0.15 phr MgO; 4 phr Escorez 1102) were added, the mixing chamber was closed again, and mixing was carried out for a total mixing time of 2 min. The filling device of the mixing chamber was then opened, 1 / 6 of the filler amount was added, followed by 1 / 2 of the oil amount, followed by 1 / 6 of the filler amount, the mixing chamber was closed again, and mixing was carried out for a total mixing time of 4 min. The mixing chamber was then opened and 1 / 6 of the filler amount was added, followed by 1 / 2 of the oil amount, followed by 1 / 6 of the filler amount, the mixing chamber was closed again and mixing was carried out for a total mixing time of 6 minutes. The chamber was aerated after 8 minutes of total mixing time. The discharge temperature was controlled by adjusting the speed. Discharge was carried out after 10 minutes of total mixing time and the temperature of the compound was measured.

[0223] After the mixing process, the compound was removed from the mixer and cooled and homogenized in a laboratory roll mill with a medium nip width. For this purpose, the compound was first passed once through the roller nip, and the resulting compound sheet was wrapped around a "doll" and passed through the roller nip from the top six times. The sheet was then placed on a cooling table and cooled until the sheet reached room temperature.

[0224] [Table 2]

[0225] Comparative Example V1 differs from Example B1 according to the invention in that technical carbon black N660 was used in this example. Comparative Example V2 used the maximum amount (phr) of F1A permitted for HTT lignin according to the teachings of WO 2020 / 202125 A1.

[0226] Preparation of vulcanizable rubber composition (second step) The vulcanizable "green compounds" of Examples V1, V2, and B1 were prepared by incorporating for each rubber composition a vulcanization system consisting of 1 phr zinc oxide, 0.5 phr sulfur, and 1.9 phr mercaptobenzothiazyl disulfide (80%; including 20% ​​by weight of binders and dispersants). In Comparative Example V1, zinc oxide was already added in step 1.

[0227] First, the cooled compound sheet was cut into strips and the curing system chemicals were weighed out. After starting the rotor (50 rpm) at a mixing chamber temperature of 40°C, the sheet was fed into the mixing chamber, the loading device to the mixing chamber was locked pneumatically, and mixing was carried out for a total mixing time of 2 minutes. Then, the loading device to the mixing chamber was opened, the curing system chemicals were added, the loading device to the mixing chamber was locked pneumatically, and mixing was carried out for a total mixing time of 5 minutes. The discharge temperature was controlled by adjusting the speed. Discharge was carried out after 5 minutes of total mixing time and the temperature of the compound was measured.

[0228] After the mixing process, the compound was removed from the mixer and cooled and homogenized in a laboratory roll mill with a medium nip width. For this purpose, the mixture was first passed once through the roller nip, and the resulting compound sheet was rolled into a "doll" and passed six times through the roller nip from the top. The sheet was then placed on a cooling table and cooled until the sheet reached room temperature.

[0229] As a result, vulcanizable composition V1 g and V2 g and B1 g Here, "g" stands for "green compound" and the remaining notations correspond to Examples V1, V2 and B1.

[0230] Preparation of vulcanized rubber composition Vulcanizable rubber composition V1 was obtained by vulcanizing the rubber in a vulcanizing press at 160°C. g and V2 g and B1g From, vulcanizable green compound V1 g and V2 g and B1 g Corresponding fully vulcanized test sample V1 v and V2 v and B1 v The compound sheet was rolled out to a thickness of 3 mm without any wrinkles by successively narrowing the nip width of a laboratory roller. Squares measuring 250 x 250 mm were then cut out of the sheet with scissors and transferred to a press (Gibitre Instruments SRL vulcanization press with built-in mold for 2 mm thick test plates). The vulcanization time was determined by adding 1 min per mm of sheet thickness (i.e. 2 min if a 2 mm frame is used) to the t90 time measured in the rheometer test. The vulcanized rubber mat was removed immediately after the pressing time had elapsed. The mat was placed on a cooling table and allowed to cool. After cooling, the protruding edges were carefully cut off with scissors.

[0231] Further rubber compositions containing filler F1B The vulcanizable rubber compositions described in Table 3 were prepared in a manner similar to that described above. In contrast to Table 2, Table 3 designates the rubber compositions containing the ingredients and amounts added in Stage 2 (i.e., as "green compounds").

[0232] [Table 3]

[0233] Example V3 g , V4 g and B2 g Example V1 g , V2 g and B1 g (i.e., the "green compounds" of Examples V1, V2, and B1) but differ by using filler F1B instead of filler F1A. F1B has a slightly lower multipoint BET surface area and a slightly lower STSA surface area (see Table 1).

[0234] Example V5 g , V6 g and B3 g In this study, part of the filler F1B was replaced with carbon black having a different BET or STSA surface, with the ratio of FB1 to carbon black being 40:10.

[0235] Example V7 g and B4 g In this study, part of the filler F1B was replaced with carbon black having different BET or STSA surface. The ratio of FB1 to carbon black was 40:15. The process oil content was also increased slightly.

[0236] Further rubber compositions comprising filler F1C The vulcanizable rubber compositions described in Table 4 were prepared in a manner similar to that described above. The presentation in Table 4 is similar to that in Table 3.

[0237] [Table 4]

[0238] The above examples in Table 4 show that blends of bromobutyl rubber (X Butyl BB 2030) or chlorobutyl rubber (X Butyl CB 1240) with natural rubber (SMR CV) can also be produced using filler F1C. As mentioned in the results section, the use of F1 filler in bromobutyl rubber has advantages in terms of reducing gas permeability, so it is possible to maintain sufficiently good gas permeability even if part of the bromobutyl rubber is replaced by natural rubber, which has a slightly higher gas permeability but the advantage of being a product of biological origin. The advantages associated with filler F1 can also be improved by increasing the amount of F1c. The crosslinking system is adjusted to be suitable for blending with natural rubber.

[0239] <Test Results> Table 5 shows the vulcanizable rubber composition V1 g , V2 g and B1 g(Uses filler F1A) and V3 g , V4 g and B2 g The reaction rate / vulcanization rate test results (using filler F1B) are reported.

[0240] [Table 5]

[0241] As can be seen from Table 5, the reference mixture V1 using carbon black N660 g and V3 g The data for V4 is within the acceptable range. g and B2 g There is a significant difference in the reaction rates between the two. Technical literature on BIIR crosslinking with ZnO indicates that water acts as a strong retarder. The HTT lignin used reaches equilibrium at approximately 2.5% water absorption, which is significantly higher than that absorbed by Carbon Black N660. Test specimens of each mixture were then placed in T 90 By vulcanizing for a time measured for 10 min, the effect of reaction rate on vulcanization was taken into account.

[0242] Table 6 shows Comparative Example V1 v , V2 v and Example B1 of the present invention v The measured values ​​obtained for vulcanized test specimen samples are shown.

[0243] [Table 6]

[0244] As can be seen from Table 6, the use of HTT lignin improves gas permeability even at the same volume loading (considering the lower density of the filler). v A small increase in the volumetric filling level, such as B1, improves gas permeability by approximately 25%. vThe reinforcement index M300 / M100 is also improved. The values ​​of tensile strength and elongation at break are within the acceptable range for the application of the compound in the innerliner.

[0245] Table 7 shows Comparative Example V3 v , V4 v and Example B2 according to the invention v The measured values ​​obtained for vulcanized test pieces are shown.

[0246] [Table 7]

[0247] As can be seen from Table 7, when HTT lignin was used, Compound V4 v and B2 v The density of the carbon black is lower. The reinforcement properties up to 300% elongation are higher than the carbon black reference, which is also evident in the reinforcement index M300 / M100. Also, the average molecular network arc length M measured by toluene swelling using the Flory-Huggins constant (0.35) c It is also important to note that, despite the high network density and high modulus up to 300% deformation, v It can be seen that the crack growth inhibition is improved for the HTT lignin-containing compound, which is more notable since the compound is subjected to higher forces at the crack location.

[0248] [Table 8]

[0249] As can be seen from Table 8, when N772 was replaced with N326, the crosslinking rate was measured and a high torque delta (M H -M L ), which indicates a higher reinforcing effect. On the other hand, M L is hardly affected by these addition amounts, which indicates that N326 has good processability.

[0250] [Table 9]

[0251] As can be seen from Table 9, the replacement of carbon black N772 with carbon black N326 increases stress values ​​(100-300% modulus), tensile strength, elongation at break, and hardness. However, what is particularly surprising is that despite these high stress values, improvements in crack growth are realized.

Claims

1. A rubber composition comprising: A rubber component including at least one halobutyl rubber selected from the group consisting of bromobutyl rubber and chlorobutyl rubber; In the range of 0.20 to 0.45 Bq / g carbon 14 C content; The carbon content is in the range of 60% to 85% by mass based on the filler excluding ash and moisture, Has acidic hydroxy groups on the surface A filler component comprising one or more fillers F1; Including, The weighted arithmetic mean of the STSA surface area of ​​filler F1 is 40 m 2 / g ~ 80m 2 / g; Filler F1 has a volume-based median particle size distribution Dv(50) in the range of 0.5 μm to 5 μm, and a volume-based Dv(97) value in the range of 3 μm to 23 μm; i. the filler component comprises more than 45 phr of filler F1; or ii. The filler component comprises more than 25 phr of a filler F1 and further comprises one or more technical carbon blacks F2, the weighted arithmetic mean STSA surface area of ​​the technical carbon blacks F2 being greater than or equal to 55 m 2 / g~95m 2 / g; A rubber composition, wherein the amount of halobutyl rubber in the rubber composition is 60 to 100 phr.

2. The STSA surface area of ​​each filler F1 is 40 m 2 / g ~ 80m 2 / g, and the STSA surface area of ​​each industrial carbon black F2 is in the range of 55 m 2 / g~95m 2 The rubber composition according to claim 1, wherein the modulus of elasticity is in the range of 1 / g.

3. The rubber composition comprises: i. a rubber other than halobutyl rubber; ii. a filler F3 different from fillers F1 and F2; iii. a softener; iv. an adhesion enhancing resin; and v. Additives for accelerating vulcanization 3. The rubber composition according to claim 1, further comprising one or more further components selected from the group consisting of:

4. i. the rubber other than the halobutyl rubber is selected from the group consisting of natural rubber, butyl rubber, and styrene-butadiene rubber; and / or ii. a filler F3 different from the fillers F1 and F2 is selected from the group of carbon black and phyllosilicates; and / or iii. the softening agent is selected from the group consisting of esters of aliphatic dicarboxylic acids, paraffinic oils, and naphthenic oils; and / or iv. the adhesion-enhancing resin is selected from the group consisting of aliphatic hydrocarbon resins, aromatic hydrocarbon resins, phenolic resins, phenol-formaldehyde resins, and phenol-acetylene resins; and / or v. The vulcanization-accelerating additive is selected from the group consisting of saturated fatty acids having 12 to 24 carbon atoms and thiazoles. The rubber composition according to claim 3 .

5. i. A rubber other than halobutyl rubber is contained in the rubber composition in an amount of 0 to 40 phr; and / or ii. A filler F3 different from the fillers F1 and F2 is contained in the rubber composition in an amount of 0 to 40 phr; and / or iii. A softener is contained in the rubber composition in an amount of 0 to 20 phr; and / or iv. An adhesion enhancing resin is included in the rubber composition in an amount of 0 to 15 phr; and / or v. Additives for accelerating vulcanization are included in the rubber composition in an amount of 0 to 5 phr. The rubber composition according to claim 3 or 4.

6. 6. A rubber composition according to claim 1, characterized in that the filler F1 is a lignin-based filler, preferably a hydrothermally treated lignin.

7. 7. The rubber composition according to claim 1 , characterized in that the one or more fillers F1 are present in an amount of 50 to 100% by weight, based on the total amount of fillers F1 and F2, and / or the total amount of fillers F1 and F2 is at least 46 phr.

8. 8. Rubber composition according to claim 1, characterized in that the amount of surface available acidic hydroxy groups of the filler F1 according to Sipponen is in the range from 0.05 mmol / g to 5 mmol / g.

9. A vulcanizable rubber composition comprising the rubber composition according to any one of claims 1 to 8 and a vulcanization system comprising zinc oxide and / or sulfur.

10. The vulcanization system is made of zinc oxide, a. at least one saturated fatty acid having 12 to 24 carbon atoms; b. at least one thiuram and / or dithiocarbamate, preferably sulfur-free; c. at least one alkylphenol disulfide; d. at least polymethylol phenolic resin or halogenated polymethylol phenolic resin, preferably free of sulfur or sulfur-containing compounds; e. sulfur and at least one thiazole and / or sulfenamide; f. sulfur, at least one thiazole and / or sulfenamide, and at least one saturated fatty acid having 12 to 24 carbon atoms; 10. The vulcanizable rubber composition of claim 9, wherein the vulcanization system is selected from the group of vulcanization systems including each of

11. A kit comprising the rubber composition (A) according to any one of claims 1 to 8 and the vulcanization system (B) according to claim 9 or 10 in a spatially separated form.

12. 9. A method for producing a rubber composition according to any one of claims 1 to 8, characterized in that a rubber component is provided and incorporated therein a filler component, and optionally softeners, adhesion enhancing resins, and additives for accelerating vulcanization.

13. 11. A method for producing a vulcanizable rubber composition according to claim 9 or 10, characterized in that in a first step, the rubber composition is prepared by the method according to claim 12, and then in a second step, the components of the vulcanization system are mixed.

14. 11. A method for further processing the vulcanizable rubber composition according to claims 9 and 10, characterized in that the vulcanizable rubber composition is formed into a web by calendaring, extrusion or roller-head processing.

15. The method according to claim 14, characterized in that the web has a thickness in the range of 0.3 to 5 mm.

16. 16. A method for manufacturing a pneumatic tire, comprising the method according to claim 14 or 15, followed by cutting the web to the size of an innerliner of a pneumatic tire, and then vulcanizing the innerliner thus obtained together with the carcass of the pneumatic tire.

17. A method for use of one or more fillers F1, optionally mixed with one or more industrial carbon blacks F2, in a rubber composition for an inner liner, wherein F1 and F2 are as defined in any one of claims 1, 6, 7 or 8, and the fillers F1 and the industrial carbon blacks F2 are used in a total amount of at least 46 phr.

18. A vulcanized rubber composition obtainable by vulcanizing the vulcanizable rubber composition according to claim 9 or 10.

19. (a) a Shore A hardness in the range of 35 to 65; and / or (b) a 300% modulus of 2.8 MPa to 8 MPa; and / or (c) 1.000g / cm 3 ~1.120g / cm 3 and / or (d) 3.8 × 10 -17 m 2 Gas permeability of less than / Pas 20. The vulcanized rubber composition of claim 18, characterized in that it has

20. 20. The vulcanized rubber composition according to claim 18 or 19, which is an inner liner of a pneumatic tire.

Citation Information

Patent Citations

  • Sulphur-linkable rubber compound, vulcanizate of the rubber compound and vehicle tyres

    EP3470457A1

  • Particulate carbon material that can be produced from renewable raw materials and method for the production of said carbon material

    WO2017085278A1

  • A tyre comprising hydrothermally carbonized lignin

    WO2017194346A1

  • Rubber compound for an innerliner

    WO2020202125A1

Cited By

  • Fluoroelastomer Compounds

    JP2025537371A